Sistem Pakar Diagnosa Penyakit Gigi Menggunakan Metode Forward Chaining Berbasis Web - rahnisa denalia (Journal of Vocational Education and Information Technology (JVEIT), 2021)
This research would discusses about applying forward chaining in designing and build expert system to diagnose toothace to help or facilitate make easier for the public society to get information and service about the indication and the illness on the teeth. The system design in this research used UML (Unifield Modeling Language) approach. The method used in this research is the forward chaining method. The result of this research is an expert in diagnosing dental disease by implementing the forward chaining method as a product that can be useful for the community. This system is expected to be a very useful tool for the community that makes it easier to get services about symptoms and diseases of the teeth.